The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fimmu.2018.03153
|View full text |Cite
|
Sign up to set email alerts
|

A Novel T-Cell Engaging Bi-specific Antibody Targeting the Leukemia Antigen PR1/HLA-A2

Abstract: Despite substantial advances in the treatment of acute myeloid leukemia (AML), only 30% of patients survive more than 5 years. Therefore, new therapeutics are much needed. Here, we present a novel therapeutic strategy targeting PR1, an HLA-A2 restricted myeloid leukemia antigen. Previously, we have developed and characterized a novel T-cell receptor-like monoclonal antibody (8F4) that targets PR1/HLA-A2 and eliminates AML xenografts by antibody-dependent cellular cytotoxicity (ADCC). To improve the potency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…The Molldrem group also developed a bsAB binding the PR1/HLA-A*02 complex and CD3 to improve the potency of the 8F4 mAB. This bsAB could activate T cells to lyse HLA-A*02 + primary AML blasts and cell lines [141]. Additionally, a TCR-like CAR with specificity for the PR1/HLA-A*02 complex, on the basis of the 8F4 mAB, was constructed, and transduced CAR T cells were capable to kill leukemia cell lines and primary AML blasts in vitro in an HLA-A*02-dependent manner [142].…”
Section: Hla-dependent Antigensmentioning
confidence: 99%
“…The Molldrem group also developed a bsAB binding the PR1/HLA-A*02 complex and CD3 to improve the potency of the 8F4 mAB. This bsAB could activate T cells to lyse HLA-A*02 + primary AML blasts and cell lines [141]. Additionally, a TCR-like CAR with specificity for the PR1/HLA-A*02 complex, on the basis of the 8F4 mAB, was constructed, and transduced CAR T cells were capable to kill leukemia cell lines and primary AML blasts in vitro in an HLA-A*02-dependent manner [142].…”
Section: Hla-dependent Antigensmentioning
confidence: 99%
“…This TCRm eliminated human AML in xenografts ( 224 ) and has now advanced to clinical trials. While active alone, to improve its potency 8F4 was engineered into a bi-specific T cell-engager (BiTE) to redirect polyclonal T cells to PR1-positive leukemias ( 225 ). The first fully human TCRm, ESK1, specific for a WT1-derived epitope/HLA-A*02:01 complex, was developed by our group ( 226 ).…”
Section: Tcr-based Non-cellular Therapiesmentioning
confidence: 99%
“…Herrmann et al also developed a TCR mimic-BiTE antibody with activity against certain tumors. (19) They used a TCR antibody (8F4) against the complex of HLA-A2 with a nonapeptide derived from proteinase-3 (P3) and neutrophil elastase (NE) (Table 1), which are highly expressed in AML blasts, multiple myeloma cells, and solid cancer. (20)(21)(22)(23)(24) It was demonstrated that 8F4 antibody can trigger CDC against AML cells in a HLA-A2-dependent manner when using AML cell lines and primary samples.…”
Section: Successful Preclinical Developmentsmentioning
confidence: 99%